Psychological and Pedagogical Foundations of Teacher Training for Development of Primary School Student’s Initial Representations (Based on The Course Material Natural Science) - Sanina S.P.; Rastorgueva M.D. (Психолого-педагогические исследования)
In 2021, a working group of the Moscow State University of Psychology and Education developed a technique for developing student’s initial representations to scientific concepts based on the material of mathematics and natural sciences in primary school. The technique was refined and concretized on the material of the course “Natural sciences”. The paper presents the materials of a study in which students of the 3rd year of the bachelor's degree program of the psychological and pedagogical direction of training (21 people, who were divided into two subgroups: experimental – 11 people, control – 10 people. The average academic performance score of each group of students is 4,7 on a five-point scale) and students of the 3rd grade of primary school of Moscow (51 people, who were also divided into two groups: experimental – 28 people, control – 23 people). The level of science literacy of primary school student’s was measured using three-level thematic tasks (author E.V. Chudinova). The results of the study showed that the application of technique for the development of primary school student’s initial natural science representations in the preparation of future teachers affects the educational results of schoolchildren. It is noted that students who designed lessons using the technique for developing student’s initial representations to scientific concepts on the material of natural sciences in primary school paid special attention not only to the correct answers of students, but also to erroneous judgments. This helped them in organizing the educational discussion. It is emphasized that an erroneous judgment can become a tool for the mental development of a primary school student’s.